Pertanggungjawaban Pidana Terhadap Korporasi yang Melakukan Tindak Pidana Perusakan Lingkungan Hidup - Wiratama, Galih Putra; Setiyono (MLJ Merdeka Law Journal, 2024)
Corporate crime lately has been seen by the public as the most serious and dangerous crimes than conventional crimes such as robbery or theft by force because the consequences of corporate crime is much more devastating than those caused by conventional crime, the purpose of this study describe and analyze criminal liability against corporations that commit crimes of environmental destruction,the formulation of the the second is how criminal liability against corporations that commit crimes of environmental destruction,the research method used is normative legal research.The first research results in UUPPLH in 2009 regulate the formulation of offenses, namely material offenses and formal offenses. Material offenses are found in Article 98, Article 99 and Article 112, while formal offenses are found in Article 100 to Article 111 and Article 113 to Article 115 of Law Number 32 of 2009 on Environmental Protection and management. While related to corporate regulation in environmental crimes stated in Article 116 paragraph (1) and Paragraph (2) and Article 118 UUPPLH. The second is the recognition of corporations as legal subjects that can be criminally liable for environmental crimes is affirmed in Article 1 Number 32 of law no. 32 of 2009 concerning the protection and management of the environment, namely “everyone is an individual or business entity, both incorporated and unincorporated” Keywords: Criminal Liability,Corporate, Environment